Template Synthesis of Oxozirconium(IV) Complexes with Tetraaza 16- and 18-Membered Macrocyclic Ligand - Yadav, H.S. (Asian Journal of Chemistry, 2010)
The macrocylic complexes of types [ZrO(mac)H2O]Cl2 or [Zr(OH)2(mac)]Cl2 (where mac = macrocyclic ligands derived by condensation of diamines with β-diketones) have been synthesized by an in situ method where the metal cation acts as a template. The isolated complexes have been characterized on the basis of elemental analyses, electrical conductance and infarared spectral data. The oxozirconium(IV) complexes are six-coordinate. The tetraaza macrocyclic ligands are coordinated to the metal ion through four azomethine nitrogen atoms.